FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI PENGGUNAAN PRODUK BANK SYARIAH DIPANDANG DARI SUDUT POTENSI EKONOMI, SIKAP, PREFERENSI KEUNTUNGAN RELATIF DENGAN KEWAJIBAN AGAMA (RELIGIOUS OBLIGATION) SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA BANK SYARIAH YANG TERDAPAT DI KOTA PEKANBARU) - Devy Tresnowati; Emrinaldi Nur DP; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
In Islam, muamalah which not allowed are those that contain elements of usury. To avoid usury which is strongly associated with the world of banking, Islamic Banks can be a solution. This study aims to examine determinant of intention to use islamic bank from the point of economic potential, attitudes, and relative advantage preferences, with attention to elements of religious obligation as a moderating variable based on the Theory of Planned Behavior. The study was conducted at ten Islamic banks and muamalat in Riau with 120 respondents. This study use multiple regression as the analytical instrument. The test results show that economic potential, attitudes and preference of relative advantage have an influence on the intentions in using Islamic banks products either directly or through moderating religious obligations. These results indicate that the economic potential and intention encourage the development of institutions and Islamic products, through moderation of religious obligations.Keywords : Intention, economic potential, attitude, preference relative advantage, religious obligations